Distribusi Manfaat Pembangunan dalam Proyek Ibu Kota Nusantara (Ikn) dan Ketimpangan Sosial: Studi Kasus Di Kalimantan Timur - Hanum Ilmiyah Mufidah; Ajeng Novillya Dhanyswara; Adelia Septiana Putri (Universitas Islam Indragiri, 2025)
The development of Indonesia’s new capital city, Ibu Kota Nusantara (IKN), in East Kalimantan is a national strategic policy aimed at promoting regional development equity and economic growth beyond Java Island. However, large-scale development projects may also generate social inequality if the distribution of benefits is uneven. This article aims to analyze how the distribution of development benefits in the IKN project contributes to social inequality in East Kalimantan. The study employs a qualitative descriptive approach using a systematic literature review method, analyzing secondary data from academic journals, government reports, statistical data, and relevant publications issued between 2020 and 2025. The findings indicate that the IKN development has positively impacted regional economic growth through increased investment, job creation, and a reduction in poverty rates. Nevertheless, these economic benefits have not been evenly distributed. The increase in the Gini Ratio reflects growing income inequality, with middle- and upper-income groups benefiting more than local communities.This article concludes that the success of the IKN development should not be measured solely by economic and infrastructural achievements, but also by its capacity to ensure inclusive and socially just development. Therefore, affirmative policies and more participatory social mitigation mechanisms are required to achieve a fair distribution of development benefits for all segments of society.